2017
DOI: 10.1136/bjsports-2017-097884
|View full text |Cite|
|
Sign up to set email alerts
|

International Olympic Committee consensus statement on pain management in elite athletes

Abstract: Pain is a common problem among elite athletes and is frequently associated with sport injury. Both pain and injury interfere with the performance of elite athletes. There are currently no evidence-based or consensusbased guidelines for the management of pain in elite athletes. Typically, pain management consists of the provision of analgesics, rest and physical therapy. More appropriately, a treatment strategy should address all contributors to pain including underlying pathophysiology, biomechanical abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
154
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 267 publications
0
154
0
5
Order By: Relevance
“…Several factors may explain delayed bedtimes and lower SE the night of competition. For example, increased circulating cortisol,74 sympathetic hyperactivity,83 elevated core body temperature84 and muscle pain85 may persist postcompetition and increase arousal 86 87. Cortisol levels following a race have been negatively (r=−0.90) correlated with SE in swimmers,32 while elevated cortisol postcompetition was associated with a reduction in TST the night of competition in netballers 74.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may explain delayed bedtimes and lower SE the night of competition. For example, increased circulating cortisol,74 sympathetic hyperactivity,83 elevated core body temperature84 and muscle pain85 may persist postcompetition and increase arousal 86 87. Cortisol levels following a race have been negatively (r=−0.90) correlated with SE in swimmers,32 while elevated cortisol postcompetition was associated with a reduction in TST the night of competition in netballers 74.…”
Section: Discussionmentioning
confidence: 99%
“…This is a concern as regular intake of analgesics may negatively affect the health . Previous studies have suggested that pain management in elite athletes should instead include strategies that address underlying biomechanical issues, pathophysiology, and psychosocial issues . For Paralympic athletes who already have existing impairments that may cause pain, it is particularly important to address these issues .…”
Section: Discussionmentioning
confidence: 99%
“…For optimal care, it is important to understand, to the extent possible, the aetiology of and influences on pain and to intervene using strategies with the optimal expected benefit and least expected harm. This narrative review underpins a broader consensus statement23 by providing an overview of the neurophysiological, biomechanical and psychosocial contributors to pain in sport.…”
Section: Introductionmentioning
confidence: 99%